Moringa Agroindustry Development Strategy (Case Study at CV Tri Utami Jaya, Mataram City) Using Analytical Hierarchy Process - Asmadi; Mohamad Harisudin; Erlyna Wida Riptanti, (International Journal of Scientific Research and Management (IJSRM), 2024)
The purpose of this study was to determine the development startegy for the moringa agroindustry. The research area was selected by purposive sampling, namely at CV. Tri Utami Jaya, Mataram City because it is the largest moringa industry  in West Nusa Tenggara Province. The processed moringa leaf products studied include moringa KIDOM tea bags and morika coffe easy. The analysis method used the Analytical Hierarchy Process (AHP). Based on the  results of the analysis, it is known that the most important priority for the moringa agroindustry development strategy is the market and marketing. The strategy to increase the market and marketing is to expand the market reach. Expanding the market reach is done by determining market segmentation, analyzing the market and using the market and using the market so that it can reach the target market. Alternative strategies that chan be applied by CV. Tri Utami Jaya are: (1) Expanding the market reach; (2) optimizing human resources (HR); (3) optimizing facilities and infrastructure; (4) preparing financial reports regularly.